FEATURES OF AXIOGRAMS IN PATIENTS WITH TEMPOROMANDIBULAR DISORDERS AND EXCESSIVE TOOTH WEAR AFTER PROSTHETIC REHABILITATION - Rybert, Y.O.; Pupin, T.I.; Magera, N.S.; Dubas, M.A.; Fetsych, O.Y.; Semchyshyn, Y.O.; Maksym, O.O. (World of Medicine and Biology, 2024)
Despite controversial statements about the correlation between temporomandibular disorders and occlusal disorders, most researchers believe that occlusion plays an important role in the etiology of temporomandibular disorders. Excessive tooth wear leads to changes in interdental relationships, insufficient interarch space for restoration or replacement of missing teeth, and positional changes in the mandible. This can result in an increased occlusal vertical dimension after prosthetic treatment, enhancing occlusal load and contributing to symptoms of temporomandibular disorders. In clinical examinations, in addition to the clinical analysis of subjective, objective, and additional methods, the method of electronic axiography with the analysis of functional occlusion in the articulator was employed. A comparative analysis of axiography results in patient groups with increased tooth wear (bruxism) combined with possible other occlusal defects (comparison group) and various forms of temporomandibular disorders: muscular, articulation, combined (main group) before and after occlusal therapy and prosthetic rehabilitation allowed us to establish a significant increase in the quality indicators of axiograms in 78.3 % of patients in the main group out of 37 examined. In the comparison group, the optimal quality of axiogram indicators increased in 83.9 % of patients, compared to 22.6 % before treatment.